Phase I Pharmacokinetic Study of Niraparib in Chinese Patients with Epithelial Ovarian Cancer. (22nd August 2019) - Zhang, Jian; Zheng, Hong; Gao, Yunong; Lou, Ge; Yin, Rutie; Ji, Dongmei; Li, Wenhua; Wang, Wei; Xia, Bairong; Wang, Danqing; Hou, Jianmei; Yan, James; et al.
Abstract: Lessons Learned: Pharmacokinetics characteristics of niraparib in Chinese patients were similar to those in white patients. Niraparib could be well tolerated by Chinese patients, and adverse events were manageable in this study. Population pharmacokinetics analysis indicated that baseline body weight had a modest impact on pharmacokinetics parameters of niraparib; however, it was not considered clinically important. Background: This randomized, open‐label, single‐arm, phase I study was designed to investigate the pharmacokinetics (PK) and safety of niraparib in Chinese patients with epithelial ovarian cancer. Methods: Eligible patients were randomized in a 1:1:1 ratio to receive 100, 200, or 300 mg of niraparib once daily. PK parameters were analyzed after single and multiple dose administrations. Results: Thirty‐six Chinese patients were enrolled in total. Niraparib was rapidly absorbed after administration, and median time‐to‐peak (Tmax ) was 3 hours. The long terminal elimination half‐life (T1/2 ∼ 35 hours) supports once‐daily dosing regimen. The exposure to niraparib showed linear and dose‐proportional pharmacokinetics, whereas other PK parameters such as Tmax, T1/2, and accumulation ratio were dose independent. Population PK analysis indicated that there was no effect of race on niraparib PK parameters, whereas baseline body weight had a modest impact on niraparib exposure. Grade 3/4 treatment‐emergent adverse events (TEAEs; reported in ≥10% of patients) included platelet count decreased (a total of five patients who were all from the 300‐mg group) and neutrophil count decreased. The TEAEs were manageable after dose modification. Conclusion: The PK profile of niraparib in Chinese patients is consistent with that in white patients. Niraparib is safe and well tolerated in Chinese patients with ovarian cancer.